2023
DOI: 10.1002/ana.26648
|View full text |Cite
|
Sign up to set email alerts
|

Choroid Plexus Enlargement Exacerbates White Matter Hyperintensity Growth through Glymphatic Impairment

Abstract: Objective: Choroid plexus (CP) is a key regulator in cerebrospinal fluid production, but its contribution to glymphatic clearance function and association with white matter hyperintensity (WMH) remains unclear. Methods: This retrospective study included 2 prospective 3.0-T magnetic resonance imaging (MRI) cohorts. In cohort 1, patients with indications for lumbar puncture underwent 3-dimensional T1-weighted sequence (3D-T1) before and at 39 hours after intrathecal administration of contrast agent (glymphatic M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…Our finding of the association between CSVD and glymphatic markers in the AD continuum was in line with previous studies focusing on CSVD patients [ 13 , 18 , 21 ]. Brain-wide network of perivascular pathways made up glymphatic system [ 49 ], so the damage of small cerebral vessels was closely correlated with glymphatic function.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our finding of the association between CSVD and glymphatic markers in the AD continuum was in line with previous studies focusing on CSVD patients [ 13 , 18 , 21 ]. Brain-wide network of perivascular pathways made up glymphatic system [ 49 ], so the damage of small cerebral vessels was closely correlated with glymphatic function.…”
Section: Discussionsupporting
confidence: 93%
“…DTI-ALPS assesses diffusivity along deep medullary veins and is suggested as a marker for evaluating glymphatic clearance function [ 17 ]. Choroid plexus volume plays a crucial role in the production of cerebrospinal fluid (CSF) and may act as a driving force for the glymphatic system [ 13 ]. Enlarged PVS observed on MRI is mostly situated around arterioles, which might cause hydrodynamic changes in CSF inflow and exchange with parenchymal fluid [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a recent neuroimaging study showed that CP enlargement was closely associated with glymphatic dysfunction [10]. Regarding the role of the glymphatic system in PD [7–9] and the relationship between CPV and glymphatic function, we can infer that CPV may play a role in the pathogenesis of PD.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a recent neuroimaging study showed that CP enlargement was closely associated with glymphatic dysfunction [10].…”
Section: Introductionmentioning
confidence: 99%